The Effect of Vidio Based Education on Adolescent Girls’ Knowledge of Vaginal Discharge Prevention - Baiq Disnalia Siswari; Eka Faizaturrahmi; Baiq Dika Fatmasari; Indriyani Makmun (Jurnal EduHealth, 2026)
One of the most common reproductive health problems in adolescent girls is vaginal discharge (Flour Albus). Flour Albus or vaginal discharge is a fluid coming out of the vagina in addition to blood. Vaginal discharge is divided into two types, namely physiological (normal) and pathological (abnormal).To determine the influence of counseling through video media on the knowledge of adolescent girls about the prevention of vaginal discharge in class X students at SMAN 1 Wanasaba. This study used a pre-experimental method with a pre-test and post-test design. The research sample of 66 people was selected using the proportional stratified random sampling technique. Data analysis used the Wilcoxon test, with a questionnaire as a research instrument. The results of the pre-test showed that most of the students had a level of knowledge in the sufficient category, namely 45 students (69.7%). After being given counseling through video media, the post-test results showed an improvement, with 65 students (98.5%) in the good category. Wilcoxon's statistical test showed a significant influence before and after health education with a p-value of 0.001 (<0.05).There is a significant influence on the increase in student's knowledge about vaginal discharge prevention after being given health education through video media